Developing bankable water reuse projects: guidelines for planners, investors, project designers and operators - International Water Management Institute (International Water Management Institute, 2023)
As water scarcity deepens across the Middle East and North Africa (MENA), IWMI’s ReWater MENA project outlines a practical roadmap for designing “bankable” water reuse models that are not only environmentally sustainable but financially viable. The brief emphasizes thinking like a business defining value propositions, targeting cost recovery, and forming innovative public-private partnerships. It introduces a five-step approach: identifying reuse options, developing business models, designing financing strategies, assessing risks, and creating implementation plans. Drawing from real cases, such as the Ouradanine treatment plant in Tunisia, the brief shows how reclaimed water and biosolids can serve agricultural needs while covering operational costs. IWMI stresses that enabling policy, legal, and institutional frameworks are essential for adoption and scale-up. With rising demand for water driven by population growth and agriculture, the guide equips governments, investors, and practitioners with actionable tools to turn water reuse into a reliable contributor to economic resilience and environmental security in the MENA region.